2018
DOI: 10.1002/dta.2527
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the in vivo metabolism of the SARM YK11: Identification and characterization of metabolites potentially useful for doping controls

Abstract: A steroidal compound was recently detected in a seized black market product and was identified as (17α,20E)-17,20-[(1-methoxyethylidene) bis (oxy)]-3-oxo-19-norpregna-4,20-diene-21-carboxylic acid methyl ester (YK11). This compound is described to possess selective androgen receptor modulator-and myostatin inhibitor-like properties. As YK11 is an experimental drug candidate and a non-approved substance for humans, scientific data on its metabolism is scarce. Due to its steroidal backbone and the arguably labil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…No drug candidate of the class of SARMs, however, has yet received clinical approval; nevertheless, the number of AAFs as the result of the presence of SARMs (or respective metabolites) in routine doping controls has continued to increase. The basis of the sensitive and specific detection of a subset of the enormous variety of SARM‐like drug candidates has been supported by sophisticated ITPs such as those reported by Ventura et al but also by identifying most adequate urinary metabolites . A comprehensive analytical assay covering a total of 15 SARMs was reported, validated for the determination of the target analytes in animal and human urine .…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…No drug candidate of the class of SARMs, however, has yet received clinical approval; nevertheless, the number of AAFs as the result of the presence of SARMs (or respective metabolites) in routine doping controls has continued to increase. The basis of the sensitive and specific detection of a subset of the enormous variety of SARM‐like drug candidates has been supported by sophisticated ITPs such as those reported by Ventura et al but also by identifying most adequate urinary metabolites . A comprehensive analytical assay covering a total of 15 SARMs was reported, validated for the determination of the target analytes in animal and human urine .…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Therefore, a GC Orbitrap system with an alternative ion source design favoring higher abundances of ions with larger m/z values was used, and the measured TMS derivatives further exhibited a reduced in-source fragmentation compared to acetates (Piper et al, 2018(Piper et al, , 2019. In addition, trimethylsilylation of steroidal analytes is routinely used, thus offering a platform for implementing potential new target analytes into sports drug testing methods.…”
Section: Limitations Of Combining Data Obtained From Gc-tc-irms/ms Lmentioning
confidence: 99%
“…ARE-luciferase reporter assay in HEK293 cells suggested that the active constituent of YK11 was 2a. Although YK11 is sold via the internet as an anabolic steroid, it is an experimental drug candidate and a non-approved substance for humans [10][11][12]. It should be noted that YK11 has not been studied in humans or even animals.…”
Section: Synthesis Of Yk11 (2a)mentioning
confidence: 99%